Does Managerial Ability Reduce Firms Cost of Debt? The Mediating Role of Earnings Quality and The Moderating Effect of Independent Commissioners - Yuliana, Nurul; Anies Lastiati (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
This study examines the impact of managerial ability on the cost of debt (COD). It also evaluates the role of earnings quality as a mediator between managerial ability and COD. It further explores the moderating role of the independent board of commissioners in the relationship between managerial ability and earnings quality. Using the path analysis method, this study analyzes data from the financial statements of manufacturing companies listed on the Indonesian Stock Exchange (IDX) from 2021 to 2023. This study finds that higher managerial ability will result in lower cost of debt. Furthermore, it indicates that managerial ability will increase firms’ earnings quality. This study also finds no evidence of a mediating effect in the relationship between managerial ability and the cost of debt. In addition, the independent board of commissioners fails to moderate the positive relationship between managerial ability and earnings quality. This study implies that managerial ability plays a key role in lowering cost of debt and improving earnings quality. It also suggests the need to enhance the effectiveness of independent commissioners and strengthen corporate governance practices.